2001
DOI: 10.1016/s0378-1097(01)00192-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of minor laccases production in the basidiomycete Marasmius quercophilus C30

Abstract: The white-rot fungus Marasmius quercophilus C30 is able to produce several laccases. The proportion of the enzymes produced depends on culture conditions. On malt medium, LAC1 was produced continuously over the 14 days of the cultivation period and was the only activity detectable. Copper increased total laccase activity by a factor 10 and induced the transient expression of one or more extra laccases in the culture medium. A combination of copper and p-hydroxybenzoic acid made it possible to extend the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 14 publications
2
37
0
1
Order By: Relevance
“…The sequences of all MREs are similar to the core MRE consensus sequence (59-TGCRCNC-39) identified in metallothionein (mt) gene promoters (Thiele, 1992). Other laccase promoters have been reported to contain multiple putative MRE sites (Karahanian et al, 1998;Mansur et al, 1998;Galhaup et al, 2002;Klonowska et al, 2001). …”
Section: Introductionmentioning
confidence: 55%
“…The sequences of all MREs are similar to the core MRE consensus sequence (59-TGCRCNC-39) identified in metallothionein (mt) gene promoters (Thiele, 1992). Other laccase promoters have been reported to contain multiple putative MRE sites (Karahanian et al, 1998;Mansur et al, 1998;Galhaup et al, 2002;Klonowska et al, 2001). …”
Section: Introductionmentioning
confidence: 55%
“…(0.05-1 mM) induced both Lac1 and Lac2. Copper is a strong inducer of laccase in many fungal species, including Trametes versicolor (L.) Lloyd (Collins and Dobson 1997), Marasmius quercophilus Pouzar (Klonowsk et al 2001), Pleurotus ostreatus (Jacq.) P. Kumm.…”
Section: Discussionmentioning
confidence: 99%
“…In response to inducers, laccase gene expression varies from fungus to fungus [23]. For example, Klonowska et al (2001) [55] showed that Marasmius quercophilus C30 produces at least four laccases. Production of two laccase forms by the fungus Volvariella volvacea was shown during induction by ferulic acid, 4-hydroxybenzoic acid, р-hydroxybenzaldehyde, veratryl acid, CuSO 4 , and xylidine [56].…”
Section: Discussionmentioning
confidence: 99%